PENGGUNAAN METODE PERMAINAN UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM OPERASI HITUNG PERKALIAN - Mochamad Guntur; Lani Robyyani (Institut Pendidikan dan Bahasa Invada, 2021)
This research is motivated by the low ability of students in multiplication arithmetic operations which is influenced by several factors including conventional learning and some students cannot do multiplication. This makes students' ability in multiplication counting operations still low. Based on these problems, efforts to improve students' abilities in multiplication counting operations using the game method. This research method uses Classroom Action Research which consists of four stages, namely; planning, implementation, observation, and reflection. This research was carried out in two cycles, where from each cycle there was a significant increase so that the game method could be applied to Mathematics